High rates of frameshift mutations within homo-oligomeric runs during a single cycle of retroviral replication. - Burns, D P (1994)
Homo-oligomeric runs were inserted into a spleen necrosis virus-based retrovirus vector to determine the nature and rate of mutations within runs of 10 to 12 identical nucleotides during a single replication cycle. Clones of helper cells containing integrated copies of retroviral vectors were used to produce virus for infection of target (nonhelper) cells. Proviral sequences from target cell clones were compared with proviral sequences from helper cell clones to study mutations that occurred during a single cycle of replication. In addition to the internal region spanning the homo-oligomeric inserts, a naturally occurring run of 10 T's in the long terminal repeat (LTR) also was sequenced. Rates of mutation ranged from < 0.01 to 0.38 frameshift mutations per run per cycle for different nucleotide runs. Frameshift mutations ranged from deletions of 2 bases to additions of 5 bases; the most common mutations were +1 and -1. Frameshift mutation rates did not increase as the run length increased from 10 to 12 bases. Rates of frameshift mutation for runs of T's and A's were significantly higher than rates for runs of C's and G's, and rates for runs of pyrimidines were significantly higher than those for runs of purines. Interestingly, the vast majority of frameshift mutations in the internal region (95%) were positive, suggesting that the primer strand tends to slip backward on the template in this region. LTR runs had a significantly lower number of positive frameshift mutations than the internal runs. By analyzing the types of frameshift mutations within runs and by comparing the patterns of frameshift mutations in the 5' and 3' LTRs of individual proviruses, we conclude that the majority of mutations observed in our system occurred during minus-strand DNA synthesis of reverse transcription.